Lipid profiles of people with human immunodeficiency virus with dyslipidemia after switching from efavirenz to dolutegravir - Supphachoke Khemla; Atibordee Meesing; Wantin Sribenjalux; Ploenchan Chetchotisakd (AboutScience Srl, 2023)
Introduction: Human immunodeficiency virus (HIV) infection and the long-term use of antiretroviral therapy, especially efavirenz (EFV)-based regimens, impact lipid profiles due to insulin resistance and lead to a higher risk of metabolic diseases. Dolutegravir (DTG) is an integrase inhibitor with better lipid profiles than EFV. However, data on treatment experience in Thailand are limited. The primary outcome was lipid profile changes at 24 weeks after switching therapy. Methods: We conducted a prospective, open-label, cohort study in people with HIV aged ≥18 years who had undergone at least 6 months of EFV-based therapy, had HIV-1 ribonucleic acid levels <50 copies/mL for ≥6 months before switching, and were diagnosed with dyslipidemia or had risk factors for atherosclerosis cardiovascular disease based on modified National Cholesterol Education Program Adult Treatment Panel III guidelines. Results: Sixty-four patients were enrolled. The mean age (standard deviation [SD]) was 48.20 ± 10.46 years, and 67.19% were male. At week 24, there were decreases from baseline in mean total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglycerides. However, mean body weight and waist circumference had increased. Conclusions: DTG resulted in better lipid profiles after switching from EFV-based therapy, suggesting that this switch could benefit patients with a high risk of cardiovascular disease. However, it is essential to note that weight gain and increased waist circumference were also observed.